Hope on the Horizon: Novel Fungal Treatments in Development. (12th January 2020) - Rauseo, Adriana M; Coler-Reilly, Ariella; Larson, Lindsey; Spec, Andrej
Abstract: The treatment of invasive fungal infections remains challenging due to limitations in currently available antifungal therapies including toxicity, interactions, restricted routes of administration, and drug resistance. This review focuses on novel therapies in clinical development, including drugs and a device. These drugs have novel mechanisms of action to overcome resistance, and some offer new formulations providing distinct advantages over current therapies to improve safety profiles and reduce interactions. Among agents that target the cell wall, 2 glucan synthesis inhibitors are discussed (rezafungin and ibrexafungerp), as well as fosmanogepix and nikkomycin Z. Agents that target the cell membrane include 3 fourth-generation azoles, oral encochleated amphotericin B, and aureobasidin A. Among agents with intracellular targets, we will review olorofim, VL-2397, T-2307, AR-12, and MGCD290. In addition, we will describe neurapheresis, a device used as adjunctive therapy for cryptococcosis. With a field full of novel treatments for fungal infections, the future looks promising. Abstract : The treatment of invasive fungal infections remains challenging. Current antifungal therapies have several limitations, including toxicities, interactions and drug-resistant fungi continue to arise. New antifungals in the pipeline will be discussed in this review.